Determination of Diastase Enzyme Activity and Water Content of Honey Forest of Sula Island, North Maluku Using Spectrophotometry Uv-Vis - Fazrul M. Yasin; Denni Afriadi; Iqbal Abdul Qutni; Maria Alexandra Karepoan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
The experiment that has been carried out aims to determine the quality of forest honey originating from the Sula Islands, North Maluku based on the parameters set by the Indonesian National Standards Agency (SNI) 8864:2018, which includes organoleptic parameters (odour and taste), water content and Diastase Number. These parameters can indicate the originality of a forest honey product. The research was conducted at the Forensic Laboratory Center of the Criminal Investigation Department of the Republic of Indonesia Police, using the laboratory experiment method, using the UV-Vis Spectrophotometry instrument, forest honey originating from the Sula Islands district, North Maluku Province was used as material in this experiment. Organoleptic tests including odour and taste were carried out using the sense of smell and taste, water content testing using an oven drying technique, and DN value determination using the UV-Vis Spectrophotometry instrument. The experiment results showed that some parameters met the requirements and did not meet the criteria. Tests on Sula Islands forest honey's taste and water content parameters did not meet the criteria, but the odour and DN parameters met the requirements.